Breath in action : the art of breath in vocal and holistic practice - Boston, Jane; Cook, Rena (Jessica Kingsley, 2009)
Breath in Action looks at the significance of breath to human life - not just the simple fact that if we stop breathing, we die, but also the more subtle ways in which our breath interacts with our voice and our being. Written by experts in vocal and holistic practice, the book is divided into four sections: Breath and the Body; Breath and the Mind; Breath and Holistic Practice; Breath and Performance. It offers the latest theories from a variety of disciplines on how we can be taught to breath better so as to communicate better, act or sing better, feel better, live better. Combining theory w.